9.2.

A donut-shaped space station (outer radius R) arranges for artificial gravity by spinning on the
axis of the donut with angular velocity ω . Sketch the forces on, and accelerations of, an
astronaut standing in the station
(a) as seen from an inertial frame outside the station and
(b) as seen in the astronaut's personal rest frame (which has a centripetal acceleration
2
A=ω R as seen in the inertial frame). What angular velocity is needed if R = 40 meters
and the apparent gravity is to equal the usual value of about 10 m/s 2?
(c) What is the percentage difference between the perceived g at a six-foot astronaut's feet (R =
40 m) and at his head (R = 38 m) ?

Given that the 4 3 M m Re surface of the ocean is an equipotential. where ho = 3 . To do this you need to find d by the law of cosines and then approximate d-1 using the binomial approximation. where h(θ) is measured up from the level at the point Q of Figure 9. Let h(θ) denote the height of the ocean at any point T on the surface. 2 M e do Sketch and describe the shape of the ocean's surface.] Penyelesaian : U eg ( T )−U eg ( Q ) =U tidal (Q )−U tidal ( T ) U eg ( T )−U eg ( Q ) =mgh {h is different between OT ∧OQ } 1 x U tidal=−G M m m ( + d d 2o ) 1 O U tidal (Q )=−G M m m ( + 2 √ d + rQ d o 2 o 2 ) −1 U tidal (Q )=−G M m m ( d 2o +r 2Q ) 2 { dimana r Q =Re } −1 2 2 2 U tidal (Q )=−G M m m ( d + R o e) . being very 2 Re careful to keep all terms through order ( ) do . Neglect any effects of the sun.5 and θ is the polar angle TOR of T . bearing in mind that ho << Re.13). [Hint: You will need to evaluate Utidal (T) as given by (9.6. show that h ( θ )=ho cos2 θ . with d equal to the distance MT .9.

2 −1 U tidal (Q )=−G M m m d −1 o ( ) 1+ Re d 2 o 2 −1 1 Misalkan ( ( 1+sesuatu ) 2 = 1− sesuatu 2 ) Maka : 2 U tidal (Q )= −G M m m do 1− ( 1 Re 2 d 2o ) −G M m m 1 x U tidal (T )= do + ( d d 2o ) 2 2 2 d =d o + r −2 d o r cos ( α ) 2 2 2 d =d o + r −2 d o r cos ( π −θ ) d 2=d 2o + r 2+ 2d o r cos ( θ ) . {cos ( π −θ ) =cos ⁡( π ) cos ⁡( θ)+sin ⁡( π ) sin ⁡( θ)} d= √d 2o +r 2+2 d o r cos ( θ ) −1 d =( d +r +2 d o r cos (θ ) ) 2 −1 2 2 o −1 r2 2 r d−1=d −1 o 1+ ( + cos ( θ ) d 2o d o ) 2 2 r 2r Misalkan ε= + cos ( θ ) d2o d o −1 maka: d =d ( 1+ ε ) 2 −1 −1 o ( 1+ε ) −1 2 1 ≅ 1− ε + −1 −3 2 2 1( ) 3 ε 2 ≅ 1− ε+ ε 2 2 2 2 8 1 3 2 d−1=d −1 o 1− ε + ε 2 8 ( ) .

{r ≅ R e } )] [ ] 2 G M m m 3 Re U tidal (Q )−U tidal ( T ) = cos2 ( θ ) do 2 d 2o mgh= G M m m 3 R2e do 2 d 2o [ cos 2 ( θ ) ] G Me karena g= 2 . maka Re G Me GM 3 ( )2 Re h= 3 m R 2e cos 2 ( θ ) do 2 . 2 d−1=d −1 o 1− ( ( 1 r2 2 r + 2 d 2o d o cos ( θ ) + 3 r2 2 r ) ( + cos (θ ) 8 d 2o d o )) ( )) 2 −1 d =d o 1− −1 1 r2 r 2 − cos ( θ ) + 2 do do 3 8 (( ) r2 2 do + 4 r3 3 do cos ( θ ) + 4 r2 2 do 2 cos ( θ ) ( )) 2 2 −1 d =d −1 o r r 1− 2 − cos (θ ) + 2 do do 3 4r 8 do 2 2 cos ( θ ) ( r2 3 r2 −1 d =d o 1− −1 ( 2 do2 − r d o cos ( θ ) + 2 2 do 2 cos ( θ ) ) x=−r cos ( α ) x=−r cos ( π −θ ) x=−r cos ( θ ) −G M m m r2 3 r2 U tidal (T )= do (r 1− 2 − cos ( θ ) + 2 do do 2 2 do 2 cos (θ )+ r cos (θ ) do ) −G M m m r2 3 r2 U tidal (T )= do 1− 2 + ( 2 2 do 2 do cos 2 ( θ ) ) U tidal (Q )−U tidal ( T ) = −G M m m do R2 2 do [( ) ( r2 3 r2 1− e2 + 1− 2 + 2 do 2 2 do cos 2 (θ ) .

4 2 3 M m Re h= cos ( θ ) 2 M e d 3o 4 2 3 M m Re h=ho cos ( θ ) . ho= 2 M e d 3o .